Pemberdayaan UMKM Gula Aren Berbasis Kearifan Lokal di Desa Kota Jawa Kecamatan Way Khilau Kabupaten Pesawaran - Syarif, Ahmad Hazas; Hudallah, Subhan; Azriansyah, Qatrunnada; Putri, Intan Lorenza; Nopriyanti, Nopriyanti (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This community service activity aims to examine strategies for optimizing the empowerment of Micro, Small and Medium Enterprises in the production and marketing of palm sugar based on the principles of local wisdom. The method used involves observation, counseling, mentoring and implementation evaluation. This dedication contributes to further understanding of how Micro, Small and Medium Palm Sugar Enterprises can play a role in sustainable development and the local economy. The policy implications resulting from this research can help the government and other stakeholders in supporting the empowerment of Micro, Small and Medium Palm Sugar Enterprises based on local wisdom and improving the welfare of local communities